The Modeling of Competitive Positions of Enterprises of Real Sector of Economy in the Domestic Market - Kutsyk Valentuna A.; Lupak Ruslan L. (Bìznes Inform, 2017)
Topicality of rational choice of methodical instrumentaqrium in assessing competitive positions of enterprises is substantiated. A wide list of methodical approaches to assessment of competitive positions of enterprises in market environment is presented, and the spheres of their practical application, general disadvantages and advantages, are characterized. The characteristics of matrix models (GE/McKinsey, SHELL/DPM, PIMS, BCG) are presented on a selective basis, so that, proceeding from a wide range of models, supported by the proper information provision, they can be assigned as the exact ones. Given the lack of information provision, disadvantages, and advantages of existing models and considering it as a means of system management, the authors have proposed to use the map of the «portfolio of competitive advantages» in the form of a nine-celled model matrix (3x3) with two-dimensional system of coordinates. The proposed model of «competitiveness / share of the national market» is an expression of competitive position of enterprises of the real sector of economy taking into consideration dynamic influence of factors of competitive environment and, at the same time, a methodical means for substantiation of competitive strategy. However, an important step in choosing the basic variant of competitive strategy for an enterprise in the real sector of economy is to determine the functional objectives to its efficient implementation.